Correction: Elshafei et al. Opportunities for Using Analytical Hierarchy Process in Green Building Optimization. Energies 2022, 15, 4490 - Ghada Elshafei; Dušan Katunský; Martina Zeleňáková; Abdelazim Negm (Energies)
There was an error in the original publication [...]